Character Development in Today's Children: The Impact of Modern vs. Traditional Games - Dara Oktaviani; Dinie Anggraeni Dewi; Nurul Hidayah (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2022)
The purpose of this research is to identify the sorts of children's games that are now being developed, as well as to examine the role and influence of children's games on the formation of children's character. Spradley model is used in this qualitative descriptive research method. This study was done at the Bandung Regency Elementary School, with a focus on kids in second grade. Data was gathered by observation, interviews, and questionnaires. Teachers and parents were interviewed, and kids were asked to complete a questionnaire. Spradley model was then used to assess the research data. According to the findings of this survey, new games in the form of online games and a variety of sports that children enjoy are currently dominating the game market. Traditional games are still played, but the intensity is low due to the lack of introduction. All games are different and have different effects on youngsters. As a result, regardless of the type of game, how the child plays and makes the best use of the game media is the most important factor, and character education is the packaging. It makes no difference how difficult the game is if it is combined with an educational approach or character education. Parents, teachers, and children working together This is critical for the teaching method using game media to be successful. Children should enjoy the more sophisticated era, but classic games should not be neglected. This can be accomplished by blending modern and traditional games in order to entice children to play.